CASE ANALYSIS OF YOUNG MAMA (MAMAK COMPLETE URUSAN IN TREASURE OF PUSAKA) MINANGKABAU - lubis, al fikri (fakultas hukum universitas PGRI Semarang, 2018)
AbstractIndonesia, known as the motto or motto of the nation